Lightweight heat-conducting polyurethane structural adhesive and preparation method thereof
By using a lightweight thermally conductive polyurethane structural adhesive composed of components A and B in the power battery system, the heat accumulation problem between the battery modules is solved, and the lightweight and thermal insulation performance of the polyurethane structural adhesive is achieved, which improves the safety and endurance of the power battery system.
Patent Information
- Application Number
- CN202510043076.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the power battery system, with the improvement of the integration of the battery module, the reduction of the distance between modules has aggravated the heat accumulation problem, resulting in thermal runaway and safety hazards, and it is difficult for polyurethane structural glue to maintain thermal insulation performance in lightweight design.
A lightweight thermally conductive polyurethane structural adhesive is used, which consists of components A and components B. In component A, low-density diols, polyfunctional polyether polyols, aliphatic polyols and diluents are used, combined with acrylic modified epoxy resin to reduce the overall density and improve the bonding strength. Inorganic fillers and flame retardants are introduced into component B to form an efficient thermal resistance layer and protective layer to enhance thermal insulation performance.
It achieves the best balance of lightweight, excellent bonding performance and good thermal insulation performance of polyurethane structural adhesive, effectively curbs thermal runaway between battery modules, and improves the safety and endurance of the power battery system.
Smart Images

Figure BDA0005237520930000051 
Figure BDA0005237520930000061 
Figure BDA0005237520930000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polyurethane structural adhesives, and more specifically, to a lightweight thermally conductive polyurethane structural adhesive and a preparation method thereof. Background Art
[0002] As the "heart" of new energy vehicles, the performance of power batteries directly determines the vehicle's endurance, acceleration performance and overall safety. In order to meet the growing demand for endurance, the power battery system is constantly optimized and designed. Among them, the precise arrangement of battery modules to form an efficient integrated power battery pack is a key measure to improve power output. This arrangement not only maximizes the use of the limited bottom space of the vehicle, but also achieves efficient transmission and release of energy through close cooperation between modules, providing the vehicle with a strong and lasting driving force.
[0003] However, as the integration of battery modules increases, the distance between modules decreases, exacerbating the problem of heat accumulation. Once a battery module experiences thermal runaway, its heat will be more easily transferred to adjacent modules, forming a chain reaction. If the entire battery pack falls into thermal runaway, it will quickly cause the temperature inside the battery pack to rise sharply, causing extreme safety incidents such as smoke, fire, and even explosion, posing a major threat to the safety of passengers and vehicles.
[0004] In order to effectively curb the above problems, polyurethane structural adhesives are widely used for connection and thermal isolation between battery modules. With its excellent bonding strength, stable chemical properties and excellent thermal insulation and heat dissipation performance, polyurethane materials build a strong and flexible thermal insulation barrier between battery modules. This barrier can effectively block the direct transfer of heat between modules, slow down the spread of thermal runaway, and provide important guarantees for the safe and stable operation of battery packs.
[0005] Faced with the urgent need for lightweight new energy vehicles, the lightweight design of polyurethane structural adhesives has become a research hotspot. By reducing the use of high-density components and introducing lightweight materials or fillers such as hollow microspheres, the density of polyurethane structural adhesives has been successfully reduced, thereby reducing the overall weight of the power battery and improving the energy density and range. However, this often sacrifices its thermal insulation performance. Therefore, how to achieve the dual functions of lightweight and thermal insulation while maintaining the excellent bonding performance of polyurethane structural adhesives has become a problem that needs to be solved urgently. Summary of the invention
[0006] In order to prepare a polyurethane structural adhesive with good bonding, good thermal insulation and heat preservation performance and light weight, the present application provides a lightweight thermally conductive polyurethane structural adhesive and a preparation method thereof.
[0007] In a first aspect, the present application provides a lightweight thermally conductive polyurethane structural adhesive, which adopts the following technical solution: A lightweight thermally conductive polyurethane structural adhesive comprises a component A and a component B, wherein the component A is prepared from the following raw materials in the following weight percentages: Aromatic diols 5-10% Multifunctional polyether polyol 5-9% Aliphatic polyols 5-8% Chain extender 1-2% Catalyst 0.8-1.2% Acrylic modified epoxy resin 10-12% The rest is diluent Component B is prepared from the following raw materials in weight percentage: Polyether diol 40-45% Diisocyanate 10-20% Inorganic filler 20-30% Flame retardant 9-20% The remainder is silane coupling agent.
[0008] By adopting the above technical scheme, the prepared polyurethane structural adhesive has light density, good adhesion and good thermal insulation performance, which can ensure that the polyurethane structural adhesive achieves the best balance between light weight, adhesion performance and thermal insulation performance.
[0009] In the present application, low-density diols, multifunctional polyether polyols, aliphatic polyols and diluents are used as matrix materials in component A. By using them in specific amounts, the overall density of component A can be reduced. At the same time, the introduction of acrylic modified epoxy resin helps to control density while ensuring strength. At the same time, acrylic modified epoxy resin can improve the bonding strength of polyurethane structural adhesives, allowing them to form a strong adhesion layer on the surfaces of different materials, meeting the bonding requirements of complex structures such as power batteries.
[0010] 1. After the two components of B are mixed, the polymer network structure formed by chemical reaction reduces the density of the entire polyurethane structural adhesive due to the use of a large number of lightweight components, which helps to lighten components such as power batteries. In component B, by introducing inorganic fillers with heat insulation properties, the heat insulation and thermal insulation properties of the polyurethane structural adhesive can be improved without significantly increasing the density. These fillers can form an effective thermal resistance layer to reduce heat transfer. The addition of flame retardants not only improves the flame retardant properties of polyurethane structural adhesives, but may also enhance the thermal insulation effect to a certain extent, because flame retardants can form a protective layer during the combustion process to slow down the spread of heat and flames.
[0011] The polyether diol in component B reacts with diisocyanate to form a polyurethane main chain, ensuring the bonding strength of the polyurethane structural adhesive. The polyol in component A also participates in this reaction to form a complex cross-linking network, which enhances the cohesion and adhesion of the polyurethane structural adhesive. At the same time, the silane coupling agent in component B can improve the interfacial bonding between polyurethane and inorganic fillers and substrates, further enhancing the bonding strength, so that the structural adhesive can maintain a stable bonding effect in various complex environments.
[0012] Preferably, the inorganic filler is a modified inorganic filler, which is prepared by the following method: A) grinding an inorganic filler and sodium hydroxide, slowly adding water while grinding, filtering, rinsing, and drying after grinding to obtain an inorganic filler with a rough surface; B) The inorganic filler with a rough surface is heated to 300-400° C., kept warm for 1-2 hours, then heated to 700-800° C., kept warm for 30-40 minutes, and then placed in a mixed solution at a temperature of 70-80° C., stirred for 1-2 hours, filtered, and dried to obtain a modified inorganic solid filler, wherein the mixed solution is obtained by mixing water, sodium chloride, and triethanolamine diisopropyl titanate in a weight ratio of 20:(1-2):(5-8).
[0013] Preferably, the weight parts of the raw materials used to prepare the modified inorganic filler are as follows: Inorganic filler 20-30 parts 4-6 parts of sodium hydroxide 15-20 parts water Mix 20-25 parts of the solution.
[0014] By adopting the above technical scheme, the compatibility of the prepared modified inorganic filler with polyurethane is greatly improved, so that the polyurethane structural adhesive can form a stronger interface bonding force after curing, thereby improving the warming bonding performance and thermal insulation performance of the polyurethane structural adhesive, while reducing the density of the polyurethane structural adhesive.
[0015] In step A), the inorganic filler is ground with sodium hydroxide and water to make the surface of the inorganic filler rough. The rough surface increases the mechanical bite force between the filler and the polyurethane matrix, which helps to improve the bonding performance. In step B), the inorganic filler is heated and enters the mixed solution, so that the volume increases and the density decreases, which helps to achieve a lightweight design of the polyurethane structural adhesive. Triethanolamine diisopropyl titanate reacts chemically with the surface of the inorganic filler to form a chemical bond, which further enhances the bonding strength between the filler and the polyurethane, thereby improving the strength and thermal insulation performance of the polyurethane structural adhesive.
[0016] Preferably, the acrylic acid-modified epoxy resin is prepared by the following method: 1) uniformly mixing an acrylic acid monomer, an initiator and a first solvent to obtain a mixture; 2) Mix the epoxy resin and the second solvent until the epoxy resin is dissolved, raise the temperature to 105-115° C., then drop the mixture, react for 40-60 minutes, lower the temperature to 45-50° C., keep the temperature for 1-2 hours, then add ammonia water to adjust the pH to 8-9 to obtain an acrylic modified epoxy resin.
[0017] Preferably, the weight parts of the raw materials used to prepare the acrylic modified epoxy resin are as follows: Acrylic acid monomer 10-15 parts Initiator 0.5-1 part 15-20 parts of the first solvent Epoxy resin 5-10 parts 20-25 parts of the second solvent 3-5 parts of ammonia water.
[0018] By adopting the above technical scheme, the graft copolymerization reaction of acrylic monomer and epoxy resin improves the compatibility between acrylic and polyurethane systems, which helps to form a more uniform and stable cross-linking network in the polyurethane structural adhesive, thereby improving the bonding strength and thermal insulation performance of the structural adhesive, while ensuring the lightweight characteristics of the polyurethane structural adhesive.
[0019] Preferably, the aromatic diol includes at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether and bisphenol A dihydroxyethyl ether.
[0020] By adopting the above technical solution, the types of aromatic diols are optimized, the density of the polyurethane structural adhesive is further reduced, and its bonding strength and thermal insulation performance are improved.
[0021] Preferably, the multifunctional polyether polyol has a functionality of 6-8 and a molecular weight of 1000-10000.
[0022] By adopting the above technical solution, the functionality and molecular weight of the multifunctional adhesive are optimized, which can react with more isocyanate molecules to form more cross-linking points, which helps to build a more stable network structure, thereby improving the bonding performance and thermal insulation performance of the polyurethane structural adhesive, while also having the characteristics of lightweight.
[0023] Preferably, the diisocyanate is obtained by mixing hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate in a weight ratio of (3-6):1.
[0024] By adopting the above technical solution, the density of the polyurethane structural adhesive can be adjusted by mixing the two, which helps to achieve lightweight. At the same time, both can react with components such as polyols to form a polyurethane network structure, improve the excellent bonding performance of the polyurethane structural adhesive, and do not affect the thermal insulation performance of the polyurethane structure.
[0025] In a second aspect, the present application provides a method for preparing a lightweight thermally conductive polyurethane structural adhesive, using the following technical solution: A method for preparing a lightweight thermally conductive polyurethane structural adhesive comprises the following preparation steps: S1. Mix and stir aromatic diols, multifunctional polyether polyols, aliphatic polyols, catalysts and diluents, raise the temperature to 70-80°C, react for 1.5-2h, then add chain extender, acrylic acid modified epoxy resin and low-density filler, raise the temperature to 80-90°C, react for 2-3h, and obtain component A; S2, mixing polyether diol, diisocyanate, inorganic filler, flame retardant and silane coupling agent, heating to 70-80°C for reaction for 2-3h, and then vacuum degassing to obtain component B; S3. Mix component A and component B to obtain a lightweight thermally conductive polyurethane structural adhesive.
[0026] By adopting the above technical solution, the obtained lightweight thermally conductive polyurethane structural adhesive has the characteristics of low density, good adhesion and good thermal insulation performance.
[0027] In summary, this application has the following beneficial effects: 1. In this application, the overall density of the polyurethane structural adhesive can be reduced by mixing aromatic diols, multifunctional polyether polyols and aliphatic polyols in a specific ratio. At the same time, through the action of components A and B, the polyurethane structural adhesive has good bonding performance and thermal insulation performance, that is, through the formula in this application, it can ensure that the polyurethane structural adhesive achieves the best balance between lightweight, bonding performance and thermal insulation. DETAILED DESCRIPTION Example
[0028] Acrylic acid-modified epoxy resin was purchased from Shanghai Huayi Fine Chemical Co., Ltd. as model 6233E.
[0029] Polycaprolactone polyol was purchased from Hubei Maidehao Biotechnology Co., Ltd., model number MDH.
[0030] Polybutylene adipate was purchased from Green Union (Jining) Chemical Technology Co., Ltd. with the brand name HY-2022.
[0031] Poly(hexanediol adipate) was purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., model number HD / AA.
[0032] Example 1 A lightweight thermally conductive polyurethane structural adhesive is prepared by the following method: S1, 50g of aromatic diol (hydroquinone dihydroxyethyl ether), 90g of multifunctional polyether polyol, 80g of aliphatic polyol (propynyl-diethylene glycol), 20g of catalyst (tin laurate) and 628g of diluent (dodecyl glycidyl ether) were mixed and stirred, heated to 70°C, reacted for 1.5h, and then 12g of chain extender (1,4-butanediol) and 120g of acrylic acid-modified epoxy resin and 50g of low-density filler (hollow glass microspheres) were added, and the temperature was raised to 80°C, and reacted for 2h to obtain component A; S2, 400 g of polyether diol (molecular weight of 2000), 200 g of diisocyanate (diphenylmethane diisocyanate), 300 g of inorganic filler (silicon dioxide), 90 g of flame retardant (antimony trioxide) and 10 g of silane coupling agent (acetyltrimethoxysilane) were mixed and stirred, heated to 70° C. for reaction for 2 h, and then vacuum degassed to obtain component B; S3. Mix component A and component B to obtain a lightweight thermally conductive polyurethane structural adhesive.
[0033] The functionality of the multifunctional polyether polyol is 6 and the molecular weight is 1000.
[0034] The difference between Example 2-3 and Example 1 is that the types, amounts and parameters of raw materials used to prepare the lightweight thermally conductive polyurethane structural adhesive are different. The specific differences are shown in Table 1: Table 1 Types, amounts and parameters of raw materials for preparing lightweight thermally conductive polyurethane structural adhesives in Examples 1-3 Example 4 A lightweight thermally conductive polyurethane structural adhesive. The difference between this embodiment and embodiment 1 is that the inorganic filler is a modified inorganic filler, which is prepared by the following method: A) grinding 300 g of an inorganic filler (silicon dioxide) and 60 g of sodium hydroxide, slowly adding 200 g of water while grinding, filtering, rinsing, and drying to obtain a rough-surfaced inorganic filler; B) The rough surface inorganic filler is heated to 300°C, kept warm for 1 hour, then heated to 700°C, kept warm for 30 minutes, and then placed in 250g of a mixed solution at 70°C, stirred for 1 hour, filtered, and dried to obtain a modified inorganic solid filler, wherein the mixed solution is obtained by mixing water, sodium chloride and triethanolamine diisopropyl titanate in a weight ratio of 20:1:5. The difference between Example 5-6 and Example 4 is that the types, amounts and parameters of raw materials for preparing the modified inorganic filler are different, and the specific differences are shown in Table 2: Table 2 Types, amounts and parameters of raw materials used to prepare modified inorganic fillers in Implementation 4-6 Example 7 A lightweight thermally conductive polyurethane structural adhesive, the difference between this embodiment and embodiment 1 is that the acrylic acid-modified epoxy resin is prepared by the following method: 1) mixing 100 g of acrylic acid monomer (glycidyl methacrylate), 5 g of initiator (tert-amyl peroxy-2-ethylhexyl ester) and 150 g of the first solvent (ethylene glycol methyl ether) to obtain a mixture; 2) 50 g of epoxy resin and 200 g of the second solvent (ethylene glycol methyl ether) were mixed until the epoxy resin was dissolved, the temperature was raised to 105° C., the mixture was added dropwise, the reaction was carried out for 40 min, the temperature was lowered to 45° C., the reaction was kept warm for 1 h, and ammonia water was added to adjust the pH to 8 to obtain an acrylic acid-modified epoxy resin.
[0035] The epoxy resin is bisphenol A epoxy resin purchased from Shandong Luxing Chemical Co., Ltd., model E-44.
[0036] The difference between Example 8-9 and Example 7 is that the types, amounts and parameters of raw materials used to prepare the acrylic modified epoxy resin are different. The specific differences are shown in Table 3: Table 3 Types, amounts and parameters of raw materials used in preparing modified inorganic fillers in Examples 7-9 Example 10 A lightweight thermally conductive polyurethane structural adhesive. The difference between this embodiment and embodiment 4 is that the acrylic modified epoxy resin is consistent with embodiment 7.
[0037] Embodiment 11 A lightweight thermally conductive polyurethane structural adhesive. The difference between this embodiment and embodiment 1 is that the diisocyanate is obtained by mixing hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate in a weight ratio of 3:1.
[0038] Example 12 A lightweight thermally conductive polyurethane structural adhesive. The difference between this embodiment and embodiment 4 is that the diisocyanate is obtained by mixing hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate in a weight ratio of 5:1.
[0039] Embodiment 13 A lightweight thermally conductive polyurethane structural adhesive. The difference between this embodiment and embodiment 7 is that the diisocyanate is obtained by mixing hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate in a weight ratio of 6:1.
[0040] Comparative Example Comparative Example 1 A lightweight thermally conductive polyurethane structural adhesive. The difference between this comparative example and Example 1 is that butanediol is used instead of p-toluene diol.
[0041] Comparative Example 2 A lightweight thermally conductive polyurethane structural adhesive. The difference between this comparative example and Example 1 is that the multifunctional polyether polyol is replaced by a polyether polyol having a functionality of 3 and a molecular weight of 1000.
[0042] Comparative Example 3 A lightweight thermally conductive polyurethane structural adhesive. The difference between this comparative example and Example 1 is that ethylene glycol terephthalate polyol is used to replace polycaprolactone polyol.
[0043] Comparative Example 4 A lightweight thermally conductive polyurethane structural adhesive. The difference between this comparative example and Example 1 is that epoxy resin is used instead of acrylic modified epoxy resin.
[0044] The epoxy resin is bisphenol A epoxy resin purchased from Shandong Luxing Chemical Co., Ltd., model E-44.
[0045] Detection method / test method Shear strength test: The test was conducted in accordance with GB / T 7124-2008 standard. Untreated 3003 aluminum sheets (100mm*25mm*2mm) were used for bonding and preparation of shear specimens. After curing for 7 days at 23°C and 50% humidity, a tensile shear test was conducted using a universal testing machine at a tensile speed of 5mm / min.
[0046] Double 85 shear strength test after aging: 3003 aluminum and 3003 aluminum are bonded to each other to prepare shear test pieces. The shear test pieces are cured for 7 days in an environment of temperature (23±2)℃ and relative humidity (50±5)%RH, and then placed in a test box at temperature 85℃ and relative humidity 85%RH for aging for 1000h. Take them out and place them at room temperature for 24h, test the shear strength, and calculate the shear strength change rate before and after aging.
[0047] Thermal conductivity test: The test is carried out in accordance with ISO22007-2 standard. The lightweight thermal conductive polyurethane structural adhesive is made into a test block with a side length of not less than 36mm and a thickness of not less than 6mm. The test block is cured for 7 days at a temperature of 23°C and a humidity of 50%, and then tested using a Hot Disk thermal constant analyzer.
[0048] Density: The density of the mixed components A and B was tested according to ASTM 1475. The experimental data is shown in Table 4: Table 4 Experimental data of Examples 1-13 and Comparative Examples 1-4 By comparing Example 1 with Comparative Examples 1-4, the shear strength of Example 1 is greater than that of Comparative Examples 1-4, and after the aging test, the shear strength change of Comparative Examples 1-4 is greater than that of Example 1; the thermal conductivity of Example 1 is less than that of Comparative Examples 1-4; the density of Example 1 is less than that of Comparative Examples 1-4, indicating that in the present application, by using aromatic diols, multifunctional polyether polyols, aliphatic polyols and acrylic modified epoxy resins together to prepare polyurethane structural adhesives, the viscosity and thermal insulation properties of polyurethane structural adhesives can be effectively improved, and the lightweight of polyurethane structural adhesives can be further achieved.
[0049] Comparing Example 1 with Example 4-6, the shear strength of Example 4-6 is greater than that of Example 1, and after the aging test, the shear strength change of Example 4-6 is less than that of Example 1; the thermal conductivity of Example 4-6 is less than that of Example 1; the density of Example 4-6 is less than that of Example 4-6, indicating that the modified inorganic filler prepared by the present application is beneficial to improving the viscosity and thermal insulation properties of the polyurethane structural adhesive, while further realizing the lightweight of the polyurethane structural adhesive.
[0050] By comparing Example 1 with Examples 7-9, the shear strength of Example 7-9 is greater than that of Example 1, and after the aging test, the shear strength change of Example 7-9 is less than that of Example 1; the thermal conductivity of Example 7-9 is less than that of Example 1; the density of Example 7-9 is less than that of Examples 4-6; By comparing Example 4 with Example 10, the shear strength of Example 10 is greater than that of Example 4, and after the aging test, the shear strength change of Example 10 is less than that of Example 4; the thermal conductivity of Example 10 is less than that of Example 4; the density of Example 10 is less than that of Example 4; It is shown from Examples 1, 4, 7-9 and 10 that the acrylic modified epoxy resin prepared by the present application is beneficial to improving the viscosity and thermal insulation properties of the polyurethane structural adhesive, while further achieving the lightweight of the polyurethane structural adhesive.
[0051] By comparing Example 1 with Example 11, the shear strength of Example 11 is greater than that of Example 1, and after the aging test, the shear strength change of Example 11 is less than that of Example 1; the thermal conductivity of Example 11 is less than that of Example 1; the density of Example 11 is less than that of Example 1; By comparing Example 4 with Example 12, the shear strength of Example 12 is greater than that of Example 4, and after the aging test, the shear strength change of Example 12 is less than that of Example 4; the thermal conductivity of Example 12 is less than that of Example 4; the density of Example 12 is less than that of Example 4; By comparing Example 7 with Example 13, the shear strength of Example 13 is greater than that of Example 7, and after the aging test, the shear strength change of Example 13 is less than that of Example 7; the thermal conductivity of Example 13 is less than that of Example 7; the density of Example 13 is less than that of Example 7; From the experimental results of Examples 1 and 11, 4 and 12, 7 and 13, the combined use of hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate is beneficial to improving the viscosity and thermal insulation properties of the polyurethane structural adhesive, while further achieving lightweighting of the polyurethane structural adhesive.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lightweight thermally conductive polyurethane structural adhesive, characterized in that: It comprises component A and component B, wherein component A is prepared from the following raw materials in weight percentage: Aromatic diols 10-30% Multifunctional polyether polyol 10-30% Aliphatic polyol 5-8% Chain extender 1-2% Catalyst 0.8-1.2% Acrylic modified epoxy resin 10-12% Low density filler 5-40% The remaining amount is diluent; Component B is prepared from the following raw materials in weight percentage: Polyether diol 40-45% Diisocyanate 10-20% Inorganic filler 20-30% Flame retardant 9-20% The remainder is silane coupling agent.
2. A lightweight thermally conductive polyurethane structural adhesive according to claim 1, characterized in that: The inorganic filler is a modified inorganic filler, which is prepared by the following method: A) grinding the inorganic filler and sodium hydroxide, slowly adding water during grinding, filtering, rinsing, and drying after grinding to obtain the inorganic filler with a rough surface; B) The inorganic filler with a rough surface is heated to 300-400°C, kept warm for 1-2 hours, then heated to 700-800°C, kept warm for 30-40 minutes, and then placed in a mixed solution at a temperature of 70-80°C, stirred for 1-2 hours, filtered, and dried to obtain a modified inorganic solid filler, wherein the mixed solution is obtained by mixing water, sodium chloride and triethanolamine diisopropyl titanate in a weight ratio of 20: (1-2): (5-8).
3. A lightweight thermally conductive polyurethane structural adhesive according to claim 2, characterized in that: The weight parts of the raw materials used to prepare the modified inorganic filler are as follows: Inorganic filler 20-30 parts 4-6 parts of sodium hydroxide 15-20 parts water Mix 20-25 parts of the solution.
4. The lightweight thermally conductive polyurethane structural adhesive according to claim 2, characterized in that: The inorganic filler includes at least one of silicon dioxide, kaolin, talc and ceramic powder.
5. The lightweight thermally conductive polyurethane structural adhesive according to claim 1, characterized in that: The acrylic acid modified epoxy resin is prepared by the following method: 1) uniformly mixing an acrylic acid monomer, an initiator and a first solvent to obtain a mixture; 2) Mix the epoxy resin and the second solvent until the epoxy resin is dissolved, raise the temperature to 105-115°C, then drop the mixture, react for 40-60 minutes, cool to 45-50°C, keep the temperature for 1-2 hours, then add ammonia water to adjust the pH to 8-9 to obtain an acrylic modified epoxy resin.
6. A lightweight thermally conductive polyurethane structural adhesive according to claim 5, characterized in that: The weight parts of the raw materials used to prepare the acrylic acid modified epoxy resin are as follows: Acrylic acid monomer 10-15 parts Initiator 0.5-1 part 15-20 parts of the first solvent Epoxy resin 5-10 parts 20-25 parts of the second solvent 3-5 parts of ammonia water.
7. The lightweight thermally conductive polyurethane structural adhesive according to claim 1, characterized in that: The aromatic diol includes at least one of hydroquinone dihydroxyethyl ether, resorcinol dihydroxyethyl ether and bisphenol A dihydroxyethyl ether.
8. The lightweight thermally conductive polyurethane structural adhesive according to claim 1, characterized in that: The functionality of the multifunctional polyether polyol is 2-8 and the molecular weight is 1000-10000.
9. The lightweight thermally conductive polyurethane structural adhesive according to claim 1, characterized in that: The diisocyanate is obtained by mixing hexamethylene diisocyanate and hydrogenated phenylmethane diisocyanate in a weight ratio of (3-6):
1.
10. A method for preparing the lightweight thermally conductive polyurethane structural adhesive according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1. Mix and stir aromatic diols, multifunctional polyether polyols, aliphatic polyols, catalysts and diluents, raise the temperature to 70-80°C, react for 1.5-2h, then add chain extender, acrylic acid modified epoxy resin and low-density filler, raise the temperature to 80-90°C, react for 2-3h, and obtain component A; S2, mixing polyether diol, diisocyanate, inorganic filler, flame retardant and silane coupling agent, heating to 70-80°C for reaction for 2-3h, and then vacuum degassing to obtain component B; S3. Mix component A and component B to obtain a lightweight thermally conductive polyurethane structural adhesive.
Citation Information
Patent Citations
High-hardness heat-conducting polyurethane structural adhesive and preparation method thereof
CN111777983A
Polyurethane-epoxy double-component structural adhesive
CN112592688A
High-strength high-elasticity two-component polyurethane structural adhesive and preparation method thereof
CN114479751A
High-temperature-resistant heat-conducting polyurethane structural adhesive and preparation method thereof
CN115785887A